A Label-Free Electrochemical Biosensor Based on Carbon Paste Electrode Modified with Graphene and ds-DNA for the Determination of the Anti-Cancer Drug Tamoxifen. Issue 7 (17th May 2017) - Moghaddam, Hadi Mahmoudi; Beitollahi, Hadi; Dehghannoudeh, Gholamreza; Forootanfar, Hamid
Abstract : As an oral nonsteroidal antiestrogen drug, tamoxifen (TMX) has been widely utilized for the prevention and treatment of breast cancer. In the current research, using differential-pulse voltammetry (DPV), an electrochemical investigation of the interaction between TMX and salmon-sperm double-stranded DNA (ds-DNA) was conducted with a graphene paste electrode (GPE). To determine TMX, a simple and sensitive biosensor was fabricated through this interaction. A linear dynamic range between 8.0 × 10 −7 and 8.5 × 10 −5 M was exhibited by DPV for TMX. Finally this modified electrode was used for determination of TMX in TMX tablet, serum and urine samples.